If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + -4x = 7x Solving 48 + -4x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 48 + -4x + -7x = 7x + -7x Combine like terms: -4x + -7x = -11x 48 + -11x = 7x + -7x Combine like terms: 7x + -7x = 0 48 + -11x = 0 Add '-48' to each side of the equation. 48 + -48 + -11x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -11x = 0 + -48 -11x = 0 + -48 Combine like terms: 0 + -48 = -48 -11x = -48 Divide each side by '-11'. x = 4.363636364 Simplifying x = 4.363636364
| 2-(x+1)=2x-11 | | 6(3x-2)=3-2(4x+1) | | -9x+9=-6x+6 | | m/2=27 | | 7x+4=7(8)+4 | | 6(w-2)=-7w-25 | | 19x-79=12x-44 | | 8(-2x+3)=32 | | 80-2x=50 | | x-.3x=38000 | | -15x-125=-9x-83 | | -3k^2=-75 | | 6a^2-8ab=0 | | -4x+14y=2 | | -6x+25=-3x+13 | | 3p-14=p | | 18=2t+8 | | -3x-3=-2x-2 | | x^2-88=-7 | | 0.09xX=123.42 | | 11x+21=6x+11 | | p/7=28 | | 15x+50=9x+32 | | 2(3x-4)=7(2x+5) | | 3-(x+2)=1 | | -r/3≤6 | | 28=p/7 | | -20x+24=-12x+16 | | -12x+63=-8x+39 | | -9x+69=-6x+45 | | t-22.4=34.8 | | -77=-9a-5 |